PERAN DAN PELUANG SL-PHT KOMODITI LADA MEMPENGARUHI KOGNITIF PETANI PERKEBUNAN RAKYAT (Studi kasus: Propinsi Lampung) - ELIZABETH, ROOSGANDHA; HENDAYANA, RACHMAT (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005)
IPM-FL (“SL-PHT”) contained more strategy alternatives and approach to develop IPM (Integrated Pest Management) in pepper agribusiness, to improve competitive trade and commerce globalization demand like eco labeling qualification (quality improvement) and free pesticide (safety) brand image. Many IPM curriculum supported by management of IPMFL which have been prepared previously, but in practiced, pepper farmers must conducted selective depend on they needed, that is: 1) pest evaluation method; 2) making ‘Bokashi’ fertilize method; 3) specific location for repairing of fertilize dose; 4) the land preparation; 5) pepper cultivation method (planting, providing seed); 6) making of Trichoderma method. Pepper (Piper nigrum, L) is eldest product and traditional export commodity of spices which have strategic opportunities on estate agribusiness (ex. Lampung Black Pepper). However, in Lampung Province, the based on income source from coffee and other plant like rubber, beside from pepper farming system;. Black pepper from Lampung different by the other pepper only in the treatment after harvest that which dried directly without soaking and peeling. All farmers In IPM-FL participant include try out farmer groups, pure farmer group and followed farmer groups. More than 70% respondent expressed to feel knowledge after following IPM-FL.
Keywords: Integrated Pest Management, Ppepper, Agribusiness